Formation process for sodium cell interface film regulation

CN122931003APending Publication Date: 2026-10-16HUNAN HUAMI TIMES NEW ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611179200.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]以硬碳负极为负极的钠离子二次电池在首次充放电化成过程中,电解液会在电极表面发生分解并形成界面膜,该界面膜能够钝化电极表面的活性位点,减少电解液后续持续发生副反应,钠离子的半径约为1.02埃,大于锂离子约0.76埃的半径,钠离子穿过界面膜并在硬碳层间脱嵌时,容易引起较大的体积变化,使界面膜承受较为集中的应力,在传统恒流化成或阶梯恒流化成过程中,电解液中的成膜组分会在电极表面持续、集中分解,形成的界面膜主要由碳酸钠、氟化钠等无机物组成,这类界面膜中的晶粒通常较大,分布也不均匀,同时缺少有机柔性组分对体积变化产生的应力进行缓冲,电芯在后续循环过程中,钠离子反复嵌入和脱出所产生的应力容易使无机界面膜发生开裂,电解液随后会在裂缝处裸露的活性位点继续发生副反应并产生气体,进而造成电芯膨胀、内阻升高和容量快速衰减

Benefits of technology

[0018] 1. In the formation process of sodium battery cell interface film regulation, by combining low-potential low-current pre-charging with pulse charging, the film-forming additive can first form a dense inorganic inner layer rich in sodium fluoride on the surface of the hard carbon negative electrode, and then form a flexible organic outer layer on its outside. The resulting layered interface film can buffer the volume change and interface stress caused by sodium ion insertion and extraction, reduce interface film cracking, and inhibit the continuous occurrence of side reactions of electrolyte at exposed active sites, thereby reducing interface impedance and improving the stability of the interface film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931003A_ABST
    Figure CN122931003A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of secondary batteries, and discloses a formation process for sodium battery cell interface film regulation, which comprises the following steps: applying a constant pre-charging current to a target potential and a rated charge amount in an initial ambient temperature; increasing the temperature and alternately applying a pulse charging current stage and a pulse relaxation stage, collecting the voltage decay slope of the relaxation stage to dynamically update the charging current density of the subsequent period; and when the terminal voltage reaches the formation cutoff voltage, maintaining constant voltage charging under the constraint state of increasing the temperature and applying mechanical clamping pressure, the application constructs a gradient heterogeneous interface film with a dense inorganic inner layer and a high-elasticity organic outer layer, releases the lattice expansion stress, inhibits film layer cracking and side reaction gas production, reduces the interface impedance, and enhances the cycle stability of the sodium battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a formation process for regulating the interface film of sodium battery cells, belonging to the field of secondary battery technology. Background Technology

[0002] In sodium-ion secondary batteries with hard carbon anodes, during the initial charge-discharge formation process, the electrolyte decomposes on the electrode surface and forms an interfacial film. This interfacial film passivates the active sites on the electrode surface, reducing subsequent side reactions in the electrolyte. The radius of sodium ions is approximately 1.02 angstroms, larger than that of lithium ions (approximately 0.76 angstroms). When sodium ions pass through the interfacial film and are intercalated / deintercalated between the hard carbon layers, they easily cause significant volume changes, subjecting the interfacial film to concentrated stress. In traditional constant current formation or step constant current formation, the film-forming components in the electrolyte continuously and intensively decompose on the electrode surface, forming an interfacial film mainly composed of inorganic substances such as sodium carbonate and sodium fluoride. The grains in this type of interfacial film are usually large and unevenly distributed, and lack organic flexible components to buffer the stress generated by volume changes. During subsequent cycles, the stress generated by the repeated intercalation and deintercalation of sodium ions easily causes the inorganic interfacial film to crack. The electrolyte then continues to undergo side reactions and generate gas at the exposed active sites in the cracks, leading to cell expansion, increased internal resistance, and rapid capacity decay.

[0003] To improve the quality of the interfacial film formation, existing processes typically employ methods such as increasing the formation temperature or extending the constant-voltage charging time. However, simply increasing the formation temperature accelerates the dissolution of organic film-forming components in the electrolyte, causing the already formed interfacial film to repeatedly dissolve and reconstruct. Extending the constant-voltage charging time easily leads to the accumulation of gas generated by side reactions within the electrode micropores, blocking sodium ion transport channels and increasing interfacial impedance. Even without being limited to traditional thermal and pressure control methods, introducing external physical fields or adjusting process interruptions for physical venting still have insurmountable shortcomings. For example, Chinese invention patent application CN117497869A discloses a method for improving gas production during the formation of sodium-ion pouch batteries. The method involves applying an electromagnetic field and physical pressure during the formation and charging process, and interrupting the formation process when the cell is charged to 10%~20% capacity for gas extraction and sealing. However, this method, which relies on an external electromagnetic field generator and physical assistance such as mid-process unsealing, not only significantly increases the complexity of the production process and the cost of equipment investment, but also only drives the generated gas with an external field and physically extracts the surface layer without regulating the electrochemical reaction process. It is impossible to regulate the decomposition kinetics of the film-forming components at different potentials, and therefore it is still impossible to construct an inorganic and organic layered heterogeneous interface film on the electrode surface that can buffer lattice expansion stress. It is difficult to reduce the interface impedance and suppress the continuous side reaction gas generation in the subsequent cycle process.

[0004] Therefore, how to form an interface film with the above-mentioned layered structure during the formation stage, reduce the interface film impedance, and suppress the gas production from formation side reactions remains a technical problem that needs to be solved. Summary of the Invention

[0005] To address the problems in the background art, the technical solution of the present invention is as follows: A formation process for regulating the interface film of sodium battery cells, comprising the following steps:

[0006] Step S1: Place the pre-charged sodium battery cell in an initial ambient temperature of 15°C to 20°C, and apply a constant pre-charging current of 0.02C to 0.05C until the negative electrode potential of the sodium battery cell drops to the range of 1.2V to 0.8V and the cumulative charge passing through the negative electrode reaches 1.5% to 3.0% of the rated capacity;

[0007] Step S2: Adjust the ambient temperature to 25℃ to 30℃, and alternately apply pulse charging current stage and pulse relaxation stage to the sodium battery cell; collect the first terminal voltage when the pulse charging current stage ends and the second terminal voltage when the pulse relaxation stage ends, divide the difference between the first terminal voltage and the second terminal voltage by the duration of the pulse relaxation stage to obtain the attenuation slope; when the attenuation slope is greater than the preset reference slope, subtract 1 from the quotient of the attenuation slope divided by the preset reference slope to obtain the first difference, multiply the first difference by the attenuation ratio factor of 0.10 to 0.20 to obtain the second difference, set the second difference by subtracting 1 from the second difference as the adjustment coefficient, and multiply the charging current density of the current cycle by the adjustment coefficient to set the charging current density of the next cycle;

[0008] Step S3: When the terminal voltage rises to the formation cutoff voltage of 3.8V to 4.0V, the ambient temperature is raised to 40°C to 45°C, and a mechanical clamping pressure of 0.1MPa to 0.3MPa is applied to the surface of the sodium cell. Under the physical constraint of the mechanical clamping pressure, the formation cutoff voltage is maintained for charging for 1h to 2h.

[0009] Preferably, step S2 includes the following sub-steps: step S21, acquiring the AC noise amplitude of the voltage signal during the pulse relaxation phase; step S22, when the AC noise amplitude exceeds 5mV, stopping the acquisition of the adjustment coefficient, and keeping the charging current density of the subsequent pulse cycle constant at 0.1C, the pulse duration constant at 10s, and the relaxation duration constant at 5s.

[0010] Preferably, in step S2, the initial charging current density of the current cycle is set to 0.1C to 0.3C, the initial duration of the pulse charging current phase is set to 5s to 20s, and the initial duration of the pulse relaxation phase is set to 2s to 10s.

[0011] Preferably, the method includes the following steps following step S3: step S401, transferring the sodium cell to a packaging chamber with a vacuum environment; step S402, puncturing the air bladder area of ​​the sodium cell and extracting the internal gas to complete the secondary sealing.

[0012] Preferably, step S402 includes the following sub-steps: step S4021, controlling the sealing pressure of the secondary seal to be 0.3MPa to 0.5MPa, and controlling the encapsulation temperature to be 170°C to 190°C.

[0013] Preferably, the sodium battery cell includes a hard carbon negative electrode and a positive electrode, wherein the material of the positive electrode is selected from either layered oxide or Prussian blue.

[0014] Preferably, step S3 includes the following sub-steps: step S31, positioning the sodium battery cell in the pneumatic clamp; step S32, applying mechanical clamping pressure uniformly to the surface of the sodium battery cell by adjusting the driving air pressure of the pneumatic clamp.

[0015] Preferably, the method includes the following steps prior to step S1: step S801, injecting a formation electrolyte into the assembled cell housing to form a sodium cell; step S802, placing the sodium cell in a set high-temperature range higher than the initial ambient temperature and allowing the formation electrolyte to wet the internal electrodes.

[0016] Preferably, the electrolyte contains fluoroethylene carbonate, which undergoes a reduction reaction in the range of 1.2V to 0.8V in step S1 to form a sodium fluoride inner layer on the surface of the hard carbon negative electrode.

[0017] Compared with the prior art, the beneficial effects of the present invention are:

[0018] 1. In the formation process of sodium battery cell interface film regulation, by combining low-potential low-current pre-charging with pulse charging, the film-forming additive can first form a dense inorganic inner layer rich in sodium fluoride on the surface of the hard carbon negative electrode, and then form a flexible organic outer layer on its outside. The resulting layered interface film can buffer the volume change and interface stress caused by sodium ion insertion and extraction, reduce interface film cracking, and inhibit the continuous occurrence of side reactions of electrolyte at exposed active sites, thereby reducing interface impedance and improving the stability of the interface film.

[0019] 2. By adjusting the subsequent charging intensity in a timely manner according to the voltage change during the pulse relaxation phase, and appropriately extending the relaxation time when the interface impedance increases, excessive accumulation of charge and sodium ions on the electrode surface can be avoided, reducing local concentration polarization. This adjustment method can provide more stable conditions for the uniform distribution and cross-linking of organic film-forming components, making the composition and thickness of the interface film more uniform, reducing film defects caused by local over-reaction, and improving the consistency of the formation process.

[0020] 3. In the later stages of formation, the viscosity and surface tension of the electrolyte can be reduced by increasing the temperature and mechanical clamping pressure. This makes it easier for bubbles trapped in the electrode micropores to desorb and move towards the cell's gas bladder area. Combined with subsequent evacuation and secondary sealing, this reduces the amount of gas remaining in the electrode reaction area, preventing gas from blocking ion transport. It also helps to further stabilize the interfacial film structure, thereby reducing the cell's interfacial impedance, mitigating cell expansion, and improving the cycle stability of the sodium cell. Attached Figure Description

[0021] Fig. 1 This is a flowchart illustrating the construction process of the gradient heterogeneous interface membrane of the present invention.

[0022] Fig. 2 This is a diagram showing the dynamic adjustment of the pulsed current in this invention.

[0023] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0024] The technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application are within the scope of protection of this application.

[0025] A formation process for regulating the interface film in sodium battery cells includes the following steps:

[0026] Step S1: Place the pre-charged sodium battery cell in an initial ambient temperature of 15°C to 20°C, and apply a constant pre-charging current of 0.02C to 0.05C until the negative electrode potential of the sodium battery cell drops to the range of 1.2V to 0.8V and the cumulative charge passing through the negative electrode reaches 1.5% to 3.0% of the rated capacity;

[0027] Step S2: Adjust the ambient temperature to 25℃ to 30℃, and alternately apply pulse charging current stage and pulse relaxation stage to the sodium battery cell; collect the first terminal voltage when the pulse charging current stage ends and the second terminal voltage when the pulse relaxation stage ends, divide the difference between the first terminal voltage and the second terminal voltage by the duration of the pulse relaxation stage to obtain the attenuation slope; when the attenuation slope is greater than the preset reference slope, subtract 1 from the quotient of the attenuation slope divided by the preset reference slope to obtain the first difference, multiply the first difference by the attenuation ratio factor of 0.10 to 0.20 to obtain the second difference, set the second difference by subtracting 1 from the second difference as the adjustment coefficient, and multiply the charging current density of the current cycle by the adjustment coefficient to set the charging current density of the next cycle;

[0028] Step S3: When the terminal voltage rises to the formation cutoff voltage of 3.8V to 4.0V, the ambient temperature is raised to 40°C to 45°C, and a mechanical clamping pressure of 0.1MPa to 0.3MPa is applied to the surface of the sodium cell. Under the physical constraint of the mechanical clamping pressure, the formation cutoff voltage is maintained for charging for 1h to 2h.

[0029] Preferably, step S2 includes the following sub-steps: step S21, acquiring the AC noise amplitude of the voltage signal during the pulse relaxation phase; step S22, when the AC noise amplitude exceeds 5mV, stopping the acquisition of the adjustment coefficient, and keeping the charging current density of the subsequent pulse cycle constant at 0.1C, the pulse duration constant at 10s, and the relaxation duration constant at 5s.

[0030] Preferably, in step S2, the initial charging current density of the current cycle is set to 0.1C to 0.3C, the initial duration of the pulse charging current phase is set to 5s to 20s, and the initial duration of the pulse relaxation phase is set to 2s to 10s.

[0031] Preferably, the method includes the following steps following step S3: step S401, transferring the sodium cell to a packaging chamber with a vacuum environment; step S402, puncturing the air bladder area of ​​the sodium cell and extracting the internal gas to complete the secondary sealing.

[0032] Preferably, step S402 includes the following sub-steps: step S4021, controlling the sealing pressure of the secondary seal to be 0.3MPa to 0.5MPa, and controlling the encapsulation temperature to be 170°C to 190°C.

[0033] Preferably, the sodium battery cell includes a hard carbon negative electrode and a positive electrode, wherein the material of the positive electrode is selected from either layered oxide or Prussian blue.

[0034] Preferably, step S3 includes the following sub-steps: step S31, positioning the sodium battery cell in the pneumatic clamp; step S32, applying mechanical clamping pressure uniformly to the surface of the sodium battery cell by adjusting the driving air pressure of the pneumatic clamp.

[0035] Preferably, the method includes the following steps prior to step S1: step S801, injecting a formation electrolyte into the assembled cell housing to form a sodium cell; step S802, placing the sodium cell in a set high-temperature range higher than the initial ambient temperature and allowing the formation electrolyte to wet the internal electrodes.

[0036] Preferably, the electrolyte contains fluoroethylene carbonate, which undergoes a reduction reaction in the range of 1.2V to 0.8V in step S1 to form a sodium fluoride inner layer on the surface of the hard carbon negative electrode.

[0037] Example 1: For a 100Ah soft-pack sodium-ion battery, the positive electrode material is a layered oxide Na0.9Cu0.22Fe0.30Mn0.48O2, and the negative electrode material is hard carbon. During the initial charge-discharge formation stage, the sodium ion radius reaches 1.02 angstroms. When penetrating the interface film and deintercalating between the hard carbon layers, lattice volume expansion and interface stress concentration are triggered. The decomposition of the electrolyte results in the generated interface film being mainly composed of coarse inorganic crystals and lacking flexible buffers. In subsequent cycles, the coarse inorganic film layer is subjected to volume stress and local cracking occurs, leading to side reactions in the electrolyte at the active sites and the generation of carbon monoxide, carbon dioxide, and ethylene gas. This causes cell expansion and increased interface impedance. Increasing the formation temperature triggers the dissolution and reconstruction of the film-forming components during the cycle. Prolonging the constant pressure time causes the gas generated by the side reactions to accumulate in the electrode micropores, blocking the ion transport channels. It is necessary to achieve structural control of the dense inorganic inner layer and the elastic organic outer layer of the interface film during the formation stage to reduce the interface impedance and suppress the gas generated by the side reactions.

[0038] First, a formation electrolyte is injected into the assembled battery cell casing to form a sodium battery cell. The sodium battery cell is then placed in a set high-temperature range of 45°C for 24 hours to allow the formation electrolyte to wet the internal electrodes. After completing the pre-charge, the sodium battery cell is positioned in a pneumatic clamp and placed in an initial ambient temperature of 15°C. A constant pre-charge current of 0.03C (3A) is applied, causing the negative electrode potential of the sodium battery cell to drop to 0.95V, which is within the range of 1.2V to 0.8V. At this potential of 0.95V, the fluoroethylene carbonate in the formation electrolyte undergoes a reduction reaction, generating an inorganic dense crystalline layer on the surface of the hard carbon negative electrode. This layer is characterized by a continuous, seamless coverage of the active sites on the surface of the hard carbon particles. The average thickness of this layer is limited to 2nm to 5nm, the sodium fluoride phase content is not less than 85%, and the average grain size is controlled to be 4.0nm to 5.0nm. This forms an inner layer of inorganic physicochemical boundary that can block the penetration of electrolyte solvent molecules. When the negative electrode accumulates charge... When the charge reaches 2% of the rated capacity, i.e., 2Ah, constant pre-charging is stopped to control the thickness of the sodium fluoride inner layer and passivate the active sites on the surface of the hard carbon negative electrode. In the two-electrode packaging system of soft-pack sodium batteries without an internal reference electrode, the real-time acquisition of the negative electrode potential is achieved through a mapping database of the full cell terminal voltage and negative electrode potential established before the formation process. Before pre-charging, three-electrode test batteries with sodium foil reference electrodes from the same batch are used to measure the potential evolution trajectory of the hard carbon negative electrode relative to the sodium metal reference electrode at 15℃ and a small current of 0.03C, and the full cell terminal voltage is recorded simultaneously, thereby constructing a one-to-one mapping database of terminal voltage and negative electrode potential. During the actual production formation process, the positive and negative terminal voltages of the soft-pack cells are collected in real time by a high-precision voltage sensor. The control system retrieves the mapping database and obtains the negative electrode potential by looking up a table. When the obtained negative electrode potential reaches 0.95V, it is determined that the negative electrode potential has dropped to the target potential.

[0039] The ambient temperature was adjusted to 25°C, and alternating pulse charging current and pulse relaxation phases were applied to the sodium battery cell. In this embodiment, the charging current density is expressed as a multiple relative to the rated capacity. The initial charging current density of the current cycle was set to 0.10C, corresponding to the absolute charging current. The current is 10A; the total geometric area of ​​the double-sided coating of the negative electrode of the soft-pack battery cell is 5000 cm², corresponding to a surface current density of 2 mA / cm². In subsequent cycles, the charging current density, absolute charging current, and surface current density are adjusted synchronously according to the adjustment coefficient to keep the three in the same change ratio, and the initial duration of the pulse charging current stage is set. Set the duration to 10 seconds, set the current during the pulse relaxation phase to 0A, and set the initial duration of the pulse relaxation phase to [missing information]. Set to 5 seconds; preset baseline slope The attenuation ratio is 4.00 mV / s. Set to 0.150.

[0040] During a given pulse cycle, the sampling system acquires the baseline voltage just before the pulse charge is applied. Its value is 2.100V; the first terminal voltage at the moment of cutoff during the pulse charging current phase is collected. Its value is 2.150V; the voltage at the second terminal is collected at the moment the pulse relaxation phase ends after 5 seconds. Its value is 2.120V. The instantaneous voltage decay slope is calculated according to the following formula. : ,in, The instantaneous voltage decay slope, The voltage at the first terminal. This is the voltage at the second terminal. To determine the duration of the pulse relaxation phase, the difference between the first terminal voltage (2.150V) and the second terminal voltage (2.120V) is divided by 5s, yielding an instantaneous voltage decay slope of 0.00600V / s. To perform a dimensionless comparison with a pre-defined reference slope of 4.00mV / s (using mV / s as the unit of measurement), the obtained instantaneous voltage decay slope is multiplied by 1000 to complete the unit conversion and uniformly lock it to a physical dimension of 6.00mV / s. Since the preset reference slope of 6.00mV / s is greater than 4.00mV / s, 6.00mV / s is divided by 4.00mV / s, and the dimensionless quotient 1.50 is subtracted from the number 1 to obtain the first difference 0.50. The first difference 0.50 is multiplied by the attenuation ratio factor of 0.150 to obtain the second difference 0.075. The adjustment coefficient is locked at 0.925 by subtracting the second difference 0.075 from the number 1. The absolute charging current of the current cycle is then used. Adjusted from 10A to the absolute charging current for the next cycle. Its value is 9.25A, and the surface current density is adjusted from 2mA / cm² to 1.85mA / cm².

[0041] Current interfacial membrane impedance measured based on high-frequency response The comprehensive impedance evaluation parameters of the interface membrane are calculated according to the following formula. : ,in, Parameters for evaluating the overall impedance of the interfacial membrane; For the interfacial membrane impedance, This is the absolute charging current for the current cycle. The voltage at the first terminal. The baseline voltage was calculated. The value is 0.240, falling within the target range of 0.15 to 0.30, maintaining the current relaxation duration. For 5 seconds, the organic film-forming components undergo free radical polymerization driven by the pulse charging current stage. During the pulse relaxation stage, charge transfer is paused and sodium ion redistribution is promoted, causing the organic film-forming components to crosslink on the outer side of the sodium fluoride inner layer, forming a flexible organic outer interface layer. This constitutes a gradient heterogeneous interface film structure. The flexible organic outer interface layer is formed synergistically by the pulse charging current stage and the pulse relaxation stage. During the pulse charging current stage, high current density charge transfer drives the reduction reaction of the organic film-forming monomers in the electrolyte, generating free radical intermediates and initiating initial polymerization chain growth. After entering the pulse relaxation stage, the external electric current... When the current drop is 0A, free radical electron transfer is suspended. The active oligomers and long-chain free radicals generated during the charging phase undergo rearrangement and chain relaxation due to thermal diffusion in the micro-region environment without electric field bias interference. They also undergo thermal collision crosslinking and network solidification with organic solvent molecules in the micro-region. At the same time, the relaxation process eliminates the concentration polarization of sodium ions on the electrode surface, avoiding local excessive ring opening and precipitation caused by local high electric field. This allows the organic oligomers generated during the pulse charging current phase to be uniformly distributed and complete three-dimensional network crosslinking during the pulse relaxation phase, ultimately forming a highly elastic organic outer interface layer on the outer side of the sodium fluoride inner layer.

[0042] When the terminal voltage reaches the formation cutoff voltage of 3.85V, the ambient temperature is raised to 42℃. By adjusting the pneumatic clamp driving air pressure, a mechanical clamping pressure of 0.20MPa is uniformly applied to the surface of the sodium cell. The temperature rise reduces the electrolyte viscosity and surface tension to accelerate the desorption rate of trapped bubbles in the electrode micropores. Combined with the physical constraint of the mechanical clamping pressure, the electrode structure is compacted, and the gas generated by the formation side reaction is driven to migrate directionally to the gas bladder area of ​​the sodium cell. Under this constraint, a constant voltage of 3.85V is maintained for 1.5h to solidify the double-layer interface film structure. Subsequently, the sodium cell is transferred to a packaging chamber with a vacuum environment, the gas bladder area is punctured to extract the internal gas, and the secondary sealing pressure is controlled at 0.40MPa. The packaging temperature is controlled at 180℃ to complete the secondary heat sealing. This allows the gradient heterogeneous interface film to slowly release the lattice expansion stress caused by sodium ion insertion and extraction, suppress interface film cracking and continuous side reaction gas generation, reduce cell interface impedance, and improve cycle stability.

[0043] Example 2: This example uses a 100Ah soft-pack sodium-ion battery for a comparative formation process test. The negative electrode material of the cell is hard carbon, and the positive electrode material is layered oxide Na0.9Cu0.22Fe0.30Mn0.48O2. The formation electrolyte contains fluoroethylene carbonate. The current control accuracy of the charge-discharge test system is 0.05%, the voltage sampling resolution is 0.1mV, and the channel temperature control accuracy is 0.1℃. The frequency response range of the electrochemical workstation is 10μHz to 1MHz, and the sampling frequency of the transient voltage acquisition module is 100kHz. During the test, Gaussian white noise with a signal-to-noise ratio of 25dB and a power frequency interference signal with a frequency of 50Hz are superimposed on the sampling environment to simulate the electromagnetic interference of the industrial production line. The voltage sampling period during the pulse relaxation stage is set to 10ms to balance the acquisition accuracy of the instantaneous voltage decay slope and the response speed of the control system.

[0044] The experiment consisted of four experimental groups and four control groups. Experimental group one used standard process parameters: the soft-pack sodium battery cell, after completing electrolyte pre-charging and standing at 45℃ for 24 hours to allow the formation electrolyte to wet the internal electrodes, was placed in a 15℃ environment. A constant pre-charging current of 0.03C, corresponding to 3A, was applied to reduce the negative electrode potential to 0.95V. When the cumulative charge through the negative electrode reached 2% of the rated capacity, corresponding to 2Ah, the constant pre-charging was stopped. Subsequently, the ambient temperature was adjusted to 25℃, and pulse charging current and pulse relaxation phases were applied alternately. The initial charging current density was set to 0.10C, corresponding to an absolute charging current of... The initial duration of the pulse charging current phase is 10A. Set to 10 seconds to define the initial duration of the pulse relaxation phase. Set to 5 seconds, and set the preset baseline slope. Set to 4.00 mV / s, and adjust the attenuation scaling factor. Set to 0.150, and collect the instantaneous voltage decay slope during each pulse relaxation phase. Calculate the adjustment coefficient Based on this, the charging current density for the next cycle is updated, and the overall impedance evaluation parameters of the interface film are calculated. When the terminal voltage reaches the formation cutoff voltage of 3.85V, the ambient temperature is raised to 42℃, and a mechanical clamping pressure of 0.20MPa is uniformly applied to the surface of the sodium cell using a pneumatic clamp. Under this constraint, the sodium cell is charged at a constant voltage of 3.85V for 1.5h. After the constant voltage charging is completed, the sodium cell is transferred to a packaging chamber with a vacuum environment, the air bladder area is punctured and the internal gas is extracted, and a secondary sealing is completed at a sealing pressure of 0.40MPa and a packaging temperature of 180℃.

[0045] Experimental group two used the lower limit parameters of each process range: the pre-charge ambient temperature was 15℃, the constant pre-charge current was 0.02C, the negative electrode potential dropped to 1.20V, and constant pre-charging stopped when the cumulative charge through the negative electrode reached 1.5% of the rated capacity; the pulse phase ambient temperature was 25℃, the initial charging current density was 0.10C, the initial duration of the pulse charging current phase was 5s, and the initial duration of the pulse relaxation phase was 2s; the formation cutoff voltage was 3.80V, followed by heating to 40℃, applying a mechanical clamping pressure of 0.10MPa and maintaining constant voltage charging for 1.0h; the secondary sealing pressure was 0.30MPa, and the encapsulation temperature was 170℃. Group 3 used the upper limit parameters of each process range. The pre-charge ambient temperature was 20℃, the constant pre-charge current was 0.05C, the negative electrode potential dropped to 0.80V, and the constant pre-charge was stopped when the cumulative charge through the negative electrode reached 3.0% of the rated capacity. The ambient temperature of the pulse stage was 30℃, the initial charging current density was 0.30C, the initial duration of the pulse charging current stage was 20s, and the initial duration of the pulse relaxation stage was 10s. The formation cutoff voltage was 4.00V, and then the temperature was raised to 45℃. A mechanical clamping pressure of 0.30MPa was applied and constant voltage charging was maintained for 2.0h. The sealing pressure of the secondary seal was 0.50MPa, and the encapsulation temperature was 190℃.

[0046] Experiment Group 4 verified the degradation protection when AC noise exceeds the limit, based on the process parameters of Experiment Group 1. The pre-charge cutoff potential was maintained at 0.95V, and AC noise with an amplitude of 8mV was actively injected during the pulse relaxation phase. When the system detected that the AC noise amplitude exceeded 5mV, the calculation of the adjustment coefficient was stopped. The charging current density of subsequent pulse cycles is locked at 0.10C, the duration of the pulse charging current phase is locked at 10s, and the duration of the pulse relaxation phase is locked at 5s. During the fixed-sequence degradation protection period, the control system sequentially uses step median filtering and low-pass digital filtering to process the noisy terminal voltage signal, and performs real-time integration of the amount of charge accumulated during the formation process. When the filtered terminal voltage reaches 3.85V, or the accumulated charge reaches 105.0% of the cell's rated capacity, the formation process ends and enters the temperature-pressure coupling process.

[0047] Control group 1 did not set a pre-charge cutoff potential and adopted the traditional constant current formation process. Under the conditions of 25℃ environment and no mechanical clamping pressure, it was charged with a constant current of 0.05C to 3.85V, and then switched to constant voltage charging until the current decayed to 0.01C. Control group 2 also did not set a pre-charge cutoff potential, and eliminated the low-potential micro-current pre-nucleation step. It directly applied a pulse charging current stage and a pulse relaxation stage at 0.10C at 25℃ until the terminal voltage reached 3.85V. Control group 3 adjusted the pre-charge cutoff potential to 1.40V, and the other parameters were the same as those of test group 1. Control group 4 used the process parameters of test group 1 before the terminal voltage reached 3.85V, with a pre-charge cutoff potential of 0.95V. After reaching 3.85V, the ambient temperature was maintained at 25℃, no mechanical clamping pressure was applied, and constant voltage charging at 3.85V was maintained for 1.5h.

[0048] After formation was completed in each group, the interfacial membrane impedance, average particle size of the sodium fluoride inner layer, formation gas production volume, initial coulombic efficiency, and capacity retention rate after 500 cycles were measured. The average particle size of the sodium fluoride inner layer was determined using an electrochemical quartz crystal microbalance coupled with impedance spectroscopy. The battery cell was disassembled in a dry argon glove box, and a negative electrode sample with an area of ​​1.00 cm² was cut and immersed and washed three times in anhydrous dimethyl carbonate to remove residual electrolyte salts. Then, it was vacuum dried at 25°C for 2.0 h. Subsequently, the sample was placed in a micro-area measurement cell equipped with an AC conductivity detection module, and differential capacitance characteristics were tested at a potential scan rate of 0.10 mV / s. Based on the mathematical mapping relationship between the interfacial double layer capacitance and the specific surface area of ​​the inorganic crystals, the equivalent average particle size of the sodium fluoride crystals was calculated.

[0049] After completing the above treatment, the interfacial film impedance of experimental group 1 was measured. The first group had an interfacial impedance of 1.12 mΩ, an average particle size of 4.2 nm in the inner layer of sodium fluoride, a formation gas production volume of 1.15 cm³, an initial coulombic efficiency of 88.7%, and a 500-cycle capacity retention of 92.6%. The second group had an interfacial impedance of 1.25 mΩ, an average particle size of 5.8 nm in the inner layer of sodium fluoride, a formation gas production volume of 1.38 cm³, an initial coulombic efficiency of 87.9%, and a 500-cycle capacity retention of 90.8%. The third group had an interfacial impedance of 1.28 mΩ, an average particle size of 4.8 nm in the inner layer of sodium fluoride, a formation gas production volume of 1.42 cm³, an initial coulombic efficiency of 87.6%, and a 500-cycle capacity retention of 90.2%. The 500-cycle capacity retention of all three groups was higher than 90.0%.

[0050] In Experiment Group 4, after the AC noise exceeded the threshold, the system switched to fixed-sequence degrade protection. The measured interfacial membrane impedance was 1.35 mΩ, the average particle size of the sodium fluoride inner layer was 5.1 nm, the formation gas production volume was 1.55 cm³, the initial coulombic efficiency was 86.8%, and the 500-cycle capacity retention rate was 89.1%. Compared with Experiment Group 1, the interfacial membrane impedance and formation gas production volume increased under degrade protection, while the initial coulombic efficiency and cycle capacity retention rate decreased. However, the formation process still proceeded to completion according to the fixed sequence.

[0051] In control group 1, after conventional constant-current formation, the interfacial membrane impedance was 2.85 mΩ, the average particle size of the sodium fluoride inner layer was 18.5 nm, the formation gas production volume was 5.62 cm³, the initial coulombic efficiency was 81.3%, and the 500-cycle capacity retention rate was 76.2%. The coarse inorganic crystals formed by continuous electrochemical decomposition lacked the buffer of a flexible organic outer interface layer, leading to cracking and persistent side reactions under cyclic volume stress. In control group 2, after eliminating low-potential microcurrent pre-nucleation, the interfacial membrane impedance was 2.10 mΩ, the average particle size of the sodium fluoride inner layer was 14.2 nm, the formation gas production volume was 3.85 cm³, the initial coulombic efficiency was 83.5%, and the 500-cycle capacity retention rate was 80.5%. The increased and unevenly distributed sodium fluoride crystal size resulted in higher interfacial membrane impedance and formation gas production volume compared to the experimental group. In Group 1 and Control Group 3, after setting the pre-charge cutoff potential to 1.40V, the interfacial membrane impedance was 2.15mΩ, the average particle size of the sodium fluoride inner layer was 13.8nm, the formation gas production volume was 3.20cm³, the initial coulombic efficiency was 83.8%, and the 500-cycle capacity retention rate was 81.2%. Since the cutoff potential did not fall within the 1.2V to 0.8V range, a dense sodium fluoride inner layer did not form within this range. In Control Group 4, the average particle size of the sodium fluoride inner layer was 4.5nm, but by maintaining 25°C at the end of formation and without applying mechanical clamping pressure, the side reaction gas in the electrode micropores did not migrate sufficiently to the gasbag region. The measured interfacial membrane impedance was 1.82mΩ, the formation gas production volume was 4.10cm³, the initial coulombic efficiency was 85.1%, and the 500-cycle capacity retention rate was 83.0%.

[0052] In the above data, experimental groups one to three formed a sodium fluoride inner layer on the surface of the hard carbon negative electrode through low-potential constant pre-charging. Then, the process alternated between pulse charging current stage and pulse relaxation stage, and the subsequent charging current density was adjusted according to the instantaneous voltage decay slope. Finally, constant voltage charging and secondary sealing were completed under the combined action of heating and mechanical clamping pressure. Compared with the control groups, the sodium fluoride inner layer obtained by this process had a smaller particle size, reduced interfacial film impedance and formation gas volume, and improved initial coulombic efficiency and 500-cycle capacity retention rate.

[0053] Example 3: During the formation process of a soft-pack sodium-ion battery with a rated capacity of 100Ah, a preset reference slope was established. and attenuation scaling factor Through offline testing and calibration, a reference sodium battery cell that had undergone electrolyte pre-charging and was left to stand at 45°C for 24 hours to allow the formation electrolyte to wet the internal electrodes was placed in a 25°C environment. The initial charging current density was set to 0.10C, and the corresponding absolute charging current was determined. 10A; duration of the pulse charging current phase. Setting it to 10 seconds will set the duration of the pulse relaxation phase. Set to 5 seconds, collect the instantaneous voltage decay slope of the first 20 cycles without polarization accumulation and take the arithmetic mean to obtain the preset reference slope. It is 4.00mV / s, or 0.00400V / s.

[0054] The period without polarization accumulation is determined based on the terminal voltage change at the end of the pulse relaxation phase. At the instant the pulse relaxation phase ends, if the real-time rate of change of the cell terminal voltage is less than 0.50 mV / s, and the baseline voltage drift before pulse charging in two adjacent periods is not higher than 1.0 mV, then this period is included in the statistical set of the preset reference slope. If any condition is not met, then polarization accumulation is determined to exist in this period, and it is not included in the statistics. Based on this, the attenuation ratio factor is set in increments of 0.010 within the range of 0.100 to 0.200. By comparing the response curves of the charging current reduction process and formation time under different values, the determination can be made. It is 0.150.

[0055] When the attenuation ratio factor is less than 0.10, the reduction in charging current density in the next cycle is less than 2.0%. During the rapid accumulation of concentration polarization, the charging current cannot be reduced in time, resulting in local overpolarization on the surface of the hard carbon anode and sodium precipitation side reaction. The initial coulombic efficiency decreases by more than 2.5%. When the attenuation ratio factor is greater than 0.20, the charging current decays to below 0.02C within 3 cycles, the time taken for the entire formation step is extended by more than 150%, and uneven distribution of film composition occurs. Therefore, in this embodiment, the attenuation ratio factor is set in the range of 0.10 to 0.20, and 0.150 is used as the calibration value.

[0056] The closed-loop control of the pulse charging current stage and the pulse relaxation stage operates with a sampling period of 10ms. After the negative electrode potential drops to 0.95V within the range of 1.2V to 0.8V and low-potential micro-current pre-nuclearization is completed, the ambient temperature is adjusted to 25℃, and the pulse charging current stage and the pulse relaxation stage are applied alternately. The high-frequency response module acquires the baseline voltage just before the pulse charging is applied. Its value is 2.100V; the initial charging current density is set to 0.10C, corresponding to the absolute charging current. The voltage was measured at the first terminal at the moment the pulse charging current cutoff point was recorded, with a current of 10A applied continuously for 10 seconds. Its value was 2.150V. Then the charging current was reduced to 0A and the pulse relaxation phase was entered. After 5 seconds, the voltage at the second terminal was collected. Its value is 2.120V.

[0057] The voltage at the first terminal With the second terminal voltage The difference divided by the duration of the pulse relaxation phase The instantaneous voltage decay slope is obtained. The value is 0.00600V / s, or 6.00mV / s, which is greater than the preset reference slope. The adjustment coefficient for the next pulse cycle is calculated based on the preset adjustment relationship, given a value of 4.00 mV / s. The current charging current density of 0.10C in the current cycle is multiplied by the adjustment coefficient of 0.925 to obtain the charging current density of 0.0925C in the next cycle; the corresponding absolute charging current is adjusted from 10A to 9.25A.

[0058] Current interfacial membrane impedance is measured based on electrochemical impedance response. for , to the interfacial membrane impedance With the absolute charging current of the current cycle Multiply, then divide by the first terminal voltage With baseline voltage The difference is used to obtain the comprehensive impedance evaluation parameters of the interface film. The value is 0.240. If the interface film comprehensive impedance evaluation parameters are measured in subsequent cycles... If the value is greater than 0.30, the duration of the pulse relaxation phase in the next cycle will be adjusted. The time was extended by 2 seconds, from 5 seconds to 7 seconds, to allow time for the chain segment relaxation and cross-linking of the flexible organic outer interface layer.

[0059] The interfacial membrane impedance is measured online by applying a small-amplitude high-frequency AC excitation signal during the pulse relaxation phase. Two seconds after the pulse charging stops, the high-frequency response module adds a sinusoidal AC current disturbance with a frequency of 10kHz and an effective value of 50mA to the formation circuit. The disturbance signal is then injected into the main power circuit through a capacitive coupling circuit. The sampling system synchronously acquires the AC voltage response signal at both ends of the cell at a sampling frequency of 100kHz. The AC voltage signal and AC current signal are separated in the frequency domain by fast Fourier transform, and the real part of the high-frequency impedance is extracted and used as the current interfacial membrane impedance.

[0060] During impedance measurement, a high-frequency voltage sampling module with a sampling rate of 100kHz continuously extracts signals from both the positive and negative terminals within a 10ms time window. After bandpass filtering, stray voltage ripple within the 10Hz to 100kHz frequency band is separated, and the peak-to-peak value of the AC voltage waveform within this frequency band is calculated as the AC noise amplitude. If the measured peak-to-peak value of the AC noise amplitude exceeds the deterministic threshold of 5mV, the control system stops updating the adjustment coefficient. The system switches to fixed timing control, keeping the charging current density of subsequent pulse cycles constant at 0.10C, the duration of the pulse charging current phase constant at 10s, and the duration of the pulse relaxation phase constant at 5s. The formation process continues according to this timing. The AC noise amplitude threshold is determined based on the hardware accuracy of the sampling system and the calculation accuracy of the instantaneous voltage attenuation slope. The full-scale accuracy of the voltage sensor is 0.10mV. During the 5s pulse relaxation phase, the normal polarization voltage attenuation is between 10mV and 30mV. When the AC noise amplitude exceeds 5mV, the noise amplitude reaches more than 50% of the effective attenuation signal amplitude, the signal-to-noise ratio of the instantaneous voltage attenuation slope decreases, and the calculation result of the adjustment coefficient shows irregular fluctuations. Using 5mV as the threshold, the system can switch to fixed timing control when the voltage signal is unsuitable for continued closed-loop adjustment.

[0061] When the terminal voltage rises to the formation cutoff voltage of 3.85V, the ambient temperature is raised to 42℃. By adjusting the driving air pressure of the pneumatic clamp, a mechanical clamping pressure of 0.20MPa is uniformly applied to the surface of the soft-pack sodium battery cell. The temperature rise reduces the viscosity and surface tension of the formation electrolyte, and the trapped air bubbles in the electrode micropores desorb from the hard carbon micropores and the surface of the separator. The mechanical clamping pressure compacts the battery cell body and causes the desorbed air bubbles to migrate along the micropore channels to the air bladder area.

[0062] The pneumatic clamp applies a uniform pressure of 0.20 MPa to the planar area of ​​the battery cell body. The air bladder area is located outside the clamping plate and is not subject to clamping pressure. Therefore, a mechanical stress gradient from 0.20 MPa to 0.00 MPa is formed between the battery cell body and the air bladder area. After the ambient temperature rises to 42°C, the dynamic viscosity and wetting contact angle of the electrolyte decrease. The solid-liquid adhesion work of the bubbles on the surface of the hard carbon micropores and the separator decreases accordingly. Under the compaction of the battery cell body, the desorbed micron-sized bubbles are directionally floated and migrated to the air bladder area with lower stress along the micropore channels.

[0063] Under the aforementioned temperature and mechanical clamping pressure conditions, a constant voltage of 3.85V was maintained for 1.5 hours to allow the gradient heterogeneous interface film formed by the sodium fluoride inner layer and the flexible organic outer interface layer to solidify. After the constant voltage charging was completed, the soft-pack sodium battery cell was transferred to a packaging chamber with a vacuum environment. The air bladder area was punctured and the internal gas was extracted. A secondary sealing was completed at a sealing pressure of 0.40MPa and a packaging temperature of 180℃ to release the gas collected in the air bladder area and fix the structure of the gradient heterogeneous interface film.

[0064] Example 4: This example combines Figs. 1-2 The formation process used for controlling the interface film in sodium battery cells is explained, such as... Fig. 1As shown, step S1 is first executed to perform constant pre-charging to generate the sodium fluoride inner layer. When the negative electrode potential reaches the target value, step S2 is switched to alternate pulse and relaxation to generate the organic outer interface layer. During this process, the voltage decay slope is collected to update the charging current density, and the current of the next cycle is adjusted accordingly. When the terminal voltage reaches the cutoff value, step S3 is switched to heating and pressurizing constant pressure charging to solidify the gradient heterogeneous interface film. After the constant pressure constraint charging is completed, the secondary sealing is completed to discharge the internal generated gas.

[0065] like Fig. 2 As shown, in pulse alternating formation control, the AC noise amplitude is first collected. When the AC noise exceeds the threshold, it directly enters the fixed timing degradation protection. When the AC noise does not exceed the threshold, the attenuation slope is obtained and it is determined whether the attenuation slope is greater than the preset reference slope. When the attenuation slope is greater than the preset reference slope, the adjustment coefficient is obtained and the charging current of the next cycle is set accordingly. When the attenuation slope is not greater than the preset reference slope, it directly enters the next pulse cycle.

[0066] Example 5: Before the soft-pack sodium battery cell enters the formation step of the production line, the pneumatic clamp is first subjected to a no-load self-test, and the thermal field baseline calibration of the formation box is completed. In the state without battery cells loaded, the pneumatic clamp is closed to a driving air pressure of 0.20MPa. An AC excitation signal with a frequency of 10kHz and an amplitude of 10mA is applied by a high-frequency response module, and the inherent loop impedance of the contact interface between the pressure probe and the electrode tab is measured. ,when When the impedance is not greater than 0.05mΩ, the measured value shall be recorded as the zero-point compensation impedance; when... When the impedance exceeds 0.05mΩ, start the ultrasonic cleaning program of the pneumatic clamp probe until the inherent circuit impedance recovers to no more than 0.05mΩ.

[0067] The probe part of the pneumatic clamp is equipped with a miniature electrically driven ultrasonic cleaning mechanism. When the inherent circuit impedance exceeds 0.05mΩ, the control system drives the probe mold to retract 15mm, allowing the probe to enter the built-in cleaning tank. The cleaning tank is filled with anhydrous ethanol, and an ultrasonic transducer is fixed at the bottom of the tank. The ultrasonic transducer outputs an ultrasonic vibration signal with a frequency of 40kHz and a rated power of 60W to continuously clean the gold-plated contact surface of the probe for 12s to remove the lithium fluoride and oxide deposits on the surface. After cleaning, a dry nitrogen nozzle blows the probe dry with a pressure of 0.20MPa, and the probe re-extends and resets, restoring the inherent circuit impedance to the permissible range.

[0068] Subsequently, temperature signals are simultaneously acquired by the temperature sensor of the formation chamber and the infrared temperature sensor attached to the surface of the pneumatic clamp at an initial ambient temperature of 15°C, and the real-time temperature difference between the two temperature signals is calculated. ,when When the temperature is no greater than 0.1℃, complete the thermal field baseline alignment; when When the temperature exceeds 0.1℃, the measurement bias of the chamber temperature sensor is corrected by the reading of the infrared temperature sensor, so that the temperature field measurement error in the subsequent formation stage is controlled within 0.1℃.

[0069] During the alternating pulse charging current application and pulse relaxation phases, the fixture temperature rise and tab oxidation caused by continuous production alter the probe contact resistance. The sampling system acquires the baseline voltage instantaneously before the pulse charging application in each cycle. And measure the interfacial membrane impedance for the current period. The measured interfacial membrane impedance Subtract zero-point compensation impedance The corrected impedance is obtained. : To reduce the impact of probe contact resistance on the interface film impedance evaluation results, this embodiment uses impedance correction. Instead of measured interfacial membrane impedance The parameters for evaluating the overall impedance of the interfacial membrane are obtained from the following formula in the calculation. : ,in, To correct the impedance, This is the absolute charging current for the current cycle. The voltage at the first terminal. This is the baseline voltage.

[0070] When the viscosity of the electrolyte batch fluctuates, it affects the instantaneous voltage decay slope during the pulse relaxation phase. When an offset occurs, the control system recalculates the average instantaneous voltage decay slope of the previous period without polarization accumulation every 20 pulse cycles, and uses this average value to dynamically calibrate the preset reference slope. adjustment coefficient Based on this, the charging current density for the next cycle is updated according to the actual response of the current cell batch. Under the condition that the tab contact resistance increases by 0.02mΩ or the electrolyte viscosity fluctuates by 10%, the interfacial film impedance after conversion cutoff is determined. The fluctuation was controlled within 0.05 mΩ, and the volume of gas produced by the side reaction was maintained below 1.2 cm³.

[0071] Example 6: The current multi-channel formation cabinet has 128 independent temperature control and electrical detection channels. Before batch formation, a sinusoidal AC electrical excitation with a frequency of 1kHz and an amplitude of 50mA is injected into each unloaded channel. The parasitic resistance of the cables and fixture terminals of each channel is collected to form a parasitic resistance distribution vector. The channel with the largest parasitic resistance is used as the reference phase, and the hardware voltage sampling compensation offset is set for the other channels according to the reference phase. Then, the unloaded air duct circulation of the formation cabinet is started, and the heating fan is controlled to raise the temperature inside the cabinet to 42℃ at a heating rate of 2℃ / min. After the temperature sensor readings of the 128 channels reach a steady state, a temperature distribution matrix of the cabinet space is constructed. Temperature correction coefficients are generated for channels whose local temperature deviates from the average value of 42℃ by more than 0.2℃, forming a temperature correction coefficient vector.

[0072] Each channel is equipped with a 100Ah rated capacity soft-pack sodium battery cell, and the positive electrode material is a layered oxide. The negative electrode material is hard carbon. The control system reads the open-circuit voltage of each channel's soft-pack sodium cell, discarding cells with open-circuit voltages below 2.00V or above 2.20V. Qualified soft-pack sodium cells are placed in an initial ambient temperature of 15°C and a constant pre-charge current of 0.03C (3A) is applied. A high-precision voltage sensor collects the positive and negative terminal voltages of the two-electrode packaged soft-pack sodium cell in real time with a sampling period of 10ms. After reading the real-time terminal voltage values, the control system retrieves a pre-stored database of full-cell terminal voltage and negative electrode potential mapping in memory. This database was created before the formation process using three-electrode test cells from the same batch equipped with a sodium foil metal reference electrode at 15°C. The potential evolution curve of the hard carbon negative electrode relative to the sodium metal reference electrode was measured at an ambient temperature of ℃ and a constant pre-charge current of 0.03C. Discrete data pairs were established with the synchronously acquired full-cell terminal voltage. When the control system determined that the real-time calculated potential of the hard carbon negative electrode relative to the sodium metal reference electrode dropped to the target value of 0.95V within the range of 1.2V to 0.8V, it was determined that the negative electrode potential had reached the lock-up trigger state, and the fluoroethylene carbonate in the electrolyte underwent a reduction reaction at a potential of 0.95V. When the cumulative charge passing through the negative electrode reached 2% of the rated capacity, corresponding to 2Ah, the constant pre-charge was stopped, and a dense sodium fluoride inner layer of uniform thickness was formed on the surface of the hard carbon negative electrode.

[0073] The ambient temperature of the formation chamber was adjusted to 25°C. Pulse charging current and pulse relaxation phases were applied in parallel and alternately to the 128 channels of the pouch sodium cell. The initial charging current density was set to 0.10C, corresponding to an absolute charging current of... 10A; duration of the pulse charging current phase. Set the duration of the pulse relaxation phase to 10 seconds. The time is set to 5 seconds, and the current during the pulse relaxation phase is set to 0A. The control system acquires the first terminal voltage through the high-frequency response module during each pulse relaxation phase. Second terminal voltage and baseline voltage The instantaneous voltage decay slope is calculated according to the following formula. : by Indicates the current pulse cycle number, when the... The instantaneous voltage decay slope for three consecutive cycles starting from the first cycle All exceed the preset benchmark slope When the voltage is 1.5 times the value, the control system extracts the median of the instantaneous voltage decay slope of the previous 10 cycles in which no polarization accumulation occurred, and reconstructs the preset reference slope using this median. The preset reference slope in this embodiment It is 4.00 mV / s, and 1.5 times that is 6.00 mV / s.

[0074] Probe wear reduces the effective contact area of ​​the pressurized contact surface, thereby increasing the contact resistance of the main circuit. Before the pulse charging current phase ends, the charging current generates an additional ohmic voltage drop through the increased contact resistance, affecting the first terminal voltage obtained by the sampling circuit. Too high; after entering the pulse relaxation phase with a current of 0A, the ohmic voltage drop disappears, and the voltage at the second terminal... The voltage returns to the corresponding relaxation voltage, thus the first terminal voltage... With the second terminal voltage As the difference between them increases, the calculated instantaneous voltage decay slope... If a shift occurs, the preset baseline slope is reconstructed using the median slope of the previous 10 cycles in which no polarization accumulation occurred. This allows subsequent charging current adjustments to continue to be based on the actual sampling state of the current channel.

[0075] The adjustment coefficient for the next pulse cycle is calculated using the following formula. : ,in, As the attenuation scaling factor, this embodiment sets it to 0.150, and the charging current density of the current cycle is compared with the adjustment coefficient. Multiply by the product to obtain the charging current density for the next cycle, and adjust the absolute charging current for the next cycle by the same proportion. Combined with corrected impedance The comprehensive impedance evaluation parameters of the interface membrane are calculated according to the following formula. : ,in, To correct the impedance, This is the absolute charging current for the current cycle. The voltage at the first terminal. The baseline voltage is used when the interface film comprehensive impedance evaluation parameter is... When the value is greater than 0.30, the duration of the pulse relaxation phase in the next cycle will be adjusted. Extend the time by 2 seconds, adjusting from 5 seconds to 7 seconds, so that the organic film-forming components cross-link on the outer side of the sodium fluoride inner layer to form a flexible organic outer interface layer.

[0076] When the terminal voltage of the soft-pack sodium battery cell rises to the formation cutoff voltage of 3.85V, the control system starts the temperature-pressure coupling exhaust, raises the ambient temperature of the formation chamber to 42℃, and applies a mechanical clamping pressure of 0.20MPa uniformly to the surface of each channel of the soft-pack sodium battery cell through a pneumatic clamp. The temperature rise reduces the viscosity of the formation electrolyte, and the mechanical clamping pressure compacts the battery cell body. The air bubbles trapped in the electrode micropores migrate to the air bladder area. Under this constrained state, the battery cell is charged at a constant voltage of 3.85V for 1.5h, so that the gradient heterogeneous interface film formed by the sodium fluoride inner layer and the flexible organic outer interface layer is cured.

[0077] After constant voltage charging is completed, the soft-pack sodium battery cells are transferred to a packaging chamber with a vacuum environment. The air bladder area is punctured and the internal gas is extracted. Secondary sealing is completed at a sealing pressure of 0.40 MPa and a packaging temperature of 180°C. After the above multi-channel compensation and formation treatment, the interface impedance dispersion of the entire batch of soft-pack sodium battery cells is less than 3.0%, and the gas volume extracted from the air bladder area is not less than 1.10 cm³.

[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A formation process for regulating the interface film of sodium battery cells, characterized in that, Includes the following steps: Step S1: Place the pre-charged sodium battery cell in an initial ambient temperature of 15°C to 20°C, and apply a constant pre-charging current of 0.02C to 0.05C until the negative electrode potential of the sodium battery cell drops to the range of 1.2V to 0.8V and the cumulative charge passing through the negative electrode reaches 1.5% to 3.0% of the rated capacity; Step S2: Adjust the ambient temperature to 25℃ to 30℃, and alternately apply pulse charging current stage and pulse relaxation stage to the sodium battery cell; collect the first terminal voltage when the pulse charging current stage ends and the second terminal voltage when the pulse relaxation stage ends, divide the difference between the first terminal voltage and the second terminal voltage by the duration of the pulse relaxation stage to obtain the attenuation slope; when the attenuation slope is greater than the preset reference slope, subtract 1 from the quotient of the attenuation slope divided by the preset reference slope to obtain the first difference, multiply the first difference by the attenuation ratio factor of 0.10 to 0.20 to obtain the second difference, set the second difference by subtracting 1 from the second difference as the adjustment coefficient, and multiply the charging current density of the current cycle by the adjustment coefficient to set the charging current density of the next cycle; Step S3: When the terminal voltage rises to the formation cutoff voltage of 3.8V to 4.0V, the ambient temperature is raised to 40°C to 45°C, and a mechanical clamping pressure of 0.1MPa to 0.3MPa is applied to the surface of the sodium cell. Under the physical constraint of the mechanical clamping pressure, the formation cutoff voltage is maintained for charging for 1h to 2h.

2. The formation process for controlling the interface film of sodium battery cells according to claim 1, characterized in that, Step S2 includes the following sub-steps: Step S21, during the pulse relaxation phase, the AC noise amplitude of the voltage signal is acquired; Step S22, when the AC noise amplitude exceeds 5mV, the acquisition of the adjustment coefficient is stopped, and the charging current density of the subsequent pulse cycle is kept constant at 0.1C, the pulse duration is kept constant at 10s, and the relaxation duration is kept constant at 5s.

3. The formation process for controlling the interface film of sodium battery cells according to claim 1, characterized in that, In step S2, the initial charging current density of the current cycle is set to 0.1C to 0.3C, the initial duration of the pulse charging current phase is set to 5s to 20s, and the initial duration of the pulse relaxation phase is set to 2s to 10s.

4. The formation process for controlling the interface film of sodium battery cells according to claim 1, characterized in that, The steps following step S3 are included: Step S401, transferring the sodium cell to a packaging chamber with a vacuum environment; Step S402, puncturing the air bladder area of ​​the sodium cell and extracting the internal gas to complete the secondary sealing.

5. The formation process for controlling the interface film of a sodium battery cell according to claim 4, characterized in that, Step S402 includes the following sub-steps: Step S4021, controlling the sealing pressure of the secondary seal to be 0.3MPa to 0.5MPa, and controlling the encapsulation temperature to be 170℃ to 190℃.

6. The formation process for controlling the interface film of a sodium battery cell according to claim 1, characterized in that, Sodium battery cells consist of a hard carbon negative electrode and a positive electrode, with the positive electrode material selected from either layered oxide or Prussian blue.

7. The formation process for controlling the interface film of a sodium battery cell according to claim 1, characterized in that, Step S3 includes the following sub-steps: Step S31, positioning the sodium cell in the pneumatic clamp; Step S32, applying mechanical clamping pressure uniformly to the surface of the sodium cell by adjusting the driving air pressure of the pneumatic clamp.

8. The formation process for controlling the interface film of a sodium battery cell according to claim 1, characterized in that, The steps preceding step S1 are as follows: Step S801, injecting a formation electrolyte into the assembled cell housing to form a sodium cell; Step S802, placing the sodium cell in a set high-temperature range higher than the initial ambient temperature and allowing the formation electrolyte to wet the internal electrodes.

9. The formation process for controlling the interface film of a sodium battery cell according to claim 8, characterized in that, The electrolyte contains fluoroethylene carbonate, which undergoes a reduction reaction in the range of 1.2V to 0.8V in step S1, forming a sodium fluoride inner layer on the surface of the hard carbon anode.

Citation Information

Patent Citations

  • Method for improving formation gas production of sodium ion soft package battery

    CN117497869A